ANALISIS SIFAT FISIKA TANAH PADA LAHAN GAMBUT DI KECAMATAN LIANG ANGGANG KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Siti Maysarah; Yusanto Nugroho; Susilawati Susilawati (Jurnal Sylva Scienteae, 2021)
The aims at this study to: (1) Analyze the physical properties of soil on peatlands, (2) Determine peatland management efforts. This research was conducted at Jalan Suka Maju (BRG Assisted Land) in Liang Anggang District, Banjarbaru City Government, South Kalimantan Province. The results of the analysis of soil physical properties, the results of bulk density have low values, soil porosity has a higher value, particle density has a low value, soil permeability has a high value, the consistency of existing soil is soft and the maturity of sapric peat soil, Efforts in peatland management are carried out using agroforestry patterns such as (a) Keeping peat water from quickly descending from the land as the system used is closed land, (b) Making mounds for agroforestry patterns does not exceed 25-30 cm with a base width of 30-40 cm, (c) Using woody plants such as prince, galam, candlenut, petai, jengkol, besides agricultural/fruit crops such as oranges, rambutan, sapodilla, onion, pineapple, banana, chili, and corn. And the addition of fertilizer, applying lime to neutralize peat soils.Keywords: Soil Physical Characteristics, Peatlands, Management Efforts